Unveiling the Impact of Acetic Acid: Multi-Analytical Assessment for Characterizing Accelerated Aging in Raw Silk and Sappanwood-Dyed Silk - Yujie Guo; Xudong Zhou; Mengqi Wu; Wenqing Zhang (Journal of Natural Fibers)
In this study, raw and sappanwood-dyed silks were exposed to varying concentrations of acetic acid vapor to investigate aging degradation by colorimetry, SEM, FTIR, ATR-FTIR, and HPLC. The findings illustrate that acetic acid gas could lead to increase in color difference, decrease in the relative contents of crystalline regions, and changes in amino acid contents. Therefore, the aging process could be characterized as a progressive procedure: (i) initial stages were marked by color changes, (ii) gradual acid hydrolysis occurred within the protein crystalline region in the intermediate phase, and (iii) diverse trends of increase or decrease in different amino acids prevailed during the final stage of aging. Additionally, raw and sappanwood-dyed silks deteriorated further with acetic acid solution. Colorimetry and SEM showed more severe damage in dyed silk with rougher surfaces and more fiber breakage, indicating that acidic gas in water could cause greater damage and highlighted greater vulnerability of dyed silk. This study innovatively used multiple analytical methods to explore the long-term effects of acidic environments on silk and filled gaps in gas-induced aging research. It emphasized the necessity and importance of addressing gas pollution in museums and sounded the alarm of its damaging effects on silk artifacts.